Analisis Kualitatif dan Kuantitatif Kandungan Hidrokuinon dalam Krim Pemutih Wajah yang Beredar di Pasar Tradisional Kabupaten Blora Jawa Tengah - Hamzah Gita Sari; Nurul Marfu'ah; Nadia Saptarina (Pharmasipha : Pharmaceutical Journal of Islamic Pharmacy, 2022)
Beautifying self with cosmetics is one of the ways that people interested. Consumer demand for face whitening cream is so high that many manufacturers market non-certified products containing harmful ingredients such as hydroquinone. In BPOM Regulation No. 23 of 2019 the use of hydroquinone in skin whitening is no longer allowed. Whitening cream is spread in traditional markets where a place to buy and sell various of products freely. This study aims to find out whether or not hydroquinone and its content in face whitening creams are circulating in the traditional market of Blora Regency. Sampling using pusposive sampling technique in the traditional market of Blora Regency. Samples obtained from 4 traditional markets as many as 8 samples consist of 4 samples with registration number BPOM (codes A, B, C and D) and 4 samples without registration number BPOM (codes E, F, G and H). Hydroquinone content examination includes qualitative analysis with pH measurement, color reagent and TLC and quantitative analysis with UV Spectrophotometry. The results of the hydroquine standard pH measurement showed an acid pH of 3.53-3.64 positive samples i.e. E-H samples ranging from 3.30-3.64. In the color reaction hydroquinone formed a black color with sediment, and in TLC obtained a hydroquinone Rf value of 0.9610 with a positive sample Rf value ranging from 0.9444-0.9610 so that the positive result of hydroquinone in the E-H sample. Quantitative analysis using UV Spectrophotometry showed hydroquinone levels in non BPOM code samples E, F, G and H ranging from 0.00123 % - 0.00178 %.